PENINGKATAN KOMPETENSI GURU SMP KOTA PEMATANG SIANTAR MELALUI PELATIHAN PENELITIAN TINDAKAN KELAS (PTK) - Sherly Sherly; Edy Dharma; Fitria Halim; Kisno Kisno; Calen Calen (Jurnal Abdi Insani, 2023)
Professional teachers must be able to carry out dual roles as practitioners as well as researchers. As researchers, teachers are required to be able to improve the quality of learning through classroom action research to solve problems that occur in class. Even so, there are still many teachers who have not been able to carry out classroom action research properly. This community service is a classroom action research training activity for SMP Kota Pematang Siantar teachers. The purpose of this community service is to increase the ability and knowledge of SMP Kota Pematang Siantar teachers in writing class action research reports. This activity was carried out with the principles of heutagogy and direct practice. The activity was carried out at SMP Negeri 1 Pematang Siantar City on 17-22 January 2022 and was attended by 30 teachers from SMP Negeri 1 Pematang Siantar who were proposing a promotion to TMT April 2022. This community service activities were carried out through the stages of preparation, implementation and evaluation. At the preparatory stage, a pre-test was given and continued with the delivery of material related to the basic concepts of classroom action research. The implementation stage was accompanied by teacher assistance in compiling classroom action research reports based on the proposals prepared by the teacher as independent assignments. At the evaluation stage a post-test was carried out to measure the ability and knowledge of the teacher after attending the training. The evaluation results show that there were 28 reports generated from 30 participants as training outputs. In addition, there was an increase in the average score obtained from the results of the pre-test and post-test. Community service through classroom action research training has given positive results to increasing the competence of SMP Kota Pematang Siantar teachers in writing classroom action research.